Final results of establishment of the geodetic vertical second order network of Lithuania - Birvydienė, Rosita; Butkus, Algirdas; Būga, Arūnas; Dedela, Ramūnas; Kolosovskis, Ričardas; Krikštaponis, Boleslovas; Musteikis, Arvydas; Neseckas, Algirdas; Obuchovski, Romuald; Paršeliūnas, Eimuntas; Petniūnas, Marius; Petroškevičiu, Petras; et al. (International Conference “Environmental Engineering”, 2017)
The methodology of all kinds of geodetic measurements of the Geodetic Vertical Second Order Network, the information on the observation data received and main results of the accuracy estimation and adjustment of the network are presented. In 2006 the development of the Geodetic Vertical First Order Network of Lithuania was completed. It was the basis to adopt the Height System of Lithuania (LAS07). The densification of the Geodetic Vertical First Order Network started in 2010 by development of the Geodetic Vertical Second Order Network. The Second Order Network consists of 74 levelling lines, and total length of them is 3087 km. In the period of 2010–2013 the 16 levelling lines (814 km) were observed. Rest of levelling lines were observed in 2013–2016. Total number of benchmarks is 2099. The levelling was executed by digital levels Trimble DiNi12 and coded rods Nedo LD13. All ground benchmarks were positioned by GPS receivers Trimble 5700 and Trimble Zephyr Geodetic antennas. LitPOS stations served as fiducial points. The gravity accelerations at all benchmarks were observed by gravimeters Scintrex CG . The levellings of the Second Order Network carried out is characterized by high precision: the double run of one kilometre levelling RMS error does not exceeds 0.7 mm. The adjustments of the second order levelling lines applying least square method were executed separately in each region outlined by the First Order network lines and border of a country.
Keywords: levelling; digital level; vertical network; height system